Hak Pekerja Atas Penerimaan Manfaat Jaminan Hari Tua Saat Pekerja Belum Mencapai Usia 56 Tahun - Ida Nuriya Fatmawati; Asri Wijayanti (Kosmik Hukum, 2023)
Old Age Security aims to ensure that participants can live in prosperity if they have entered retirement age, are totally disabled, or die. The purpose of this study was to determine the form of legal protection for Old Age Security participants who resign and are affected by termination of employment for the benefits of Old Age Security and their legal remedies. This legal research used a statute approach. The result of this research was a form of legal protection for Old Age Security participants is to receive benefits for the total contributions paid and their development after ten years of membership, entering retirement age, death, or permanent total disability. Employers who do not register their workers in stages are threatened with administrative sanctions. Employers who do not collect, pay and deposit contributions to Insurance and Social Security (BPJS) Employment are threatened with criminal sanctions. Old Age Security benefits will be deferred until the age of 56 years if the Old Age Security participant resigns earlier. Legal remedies that can be taken by workers if they do not get Old Age Security benefits are to settle through a mediation process carried out by the Service Quality Control Unit and Participant Complaints Handling.Keywords: Old Age Security, Stop Working, Workers.